HUBUNGAN ANTARA KONSEP DIRI DAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN EFEKTIVITAS KERJA TENAGA ADMINISTRASI SEKOLAH SMP NEGERI SE-KABUPATEN ROKAN HILIR, PROVINSI RIAU (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This study aims to determine the relationship between self-concept and school leadership with the effectiveness of the administrative staff of the school SMP Negeri se-Rokan Hilir both partially and simultaneously. Data was collected using a survey method correlation approach. The sample in this study were 100 administrative staff members who were selected using random sampling techniques. Data were collected using self-developed research instruments following Linkert world scale model of the three variables, self-concept, school leadership and effectiveness. Instrument validity was tested using Pearson Product Moment and reliability of the instrument was tested using Cronbach Alpha. Data analysis requirements. Partial relationship is determined by using simple correlations and relationships simultaneously using multiple correlation. It was concluded that, from the hypothesis testing results obtained correlation coefficient the self-concept with The Effectiveness of School of 0.628 and leadership with The Effectiveness of School for 0.601 included strong category. As for multiple test results obtained value of 0.424, which means quite strong. It suggests that either partially or multiple there is a positive relationship between self-concept and the leadership of the effectiveness of administrative personnel.Keywords: self-concept, school leadership and administrative personnel effectiveness